ANALISIS PROSES RESTITUSI PAJAK PERTAMBAHAN NILAI (PPN) DALAM UPAYA MELINDUNGI HAK WAJIB PAJAK BADAN PADA KANTOR KONSULTAN PAJAK SOLUSI KONSULTAN MANDIRI - Wahyuni Wahyuni (Worksheet : Jurnal Akuntansi, 2026)
Value Added Tax (VAT) restitution is an important mechanism in the tax system to ensure fairness and protect taxpayer rights. However, in practice, it is often considered complex due to strict administrative procedures and lengthy audit processes. This study aims to analyze the VAT restitution process in an effort to protect the rights of corporate taxpayers at the Solusi Konsultan Mandiri Tax Consultant Office. This study uses a qualitative descriptive method, with data collection techniques including interviews, documentation, and observation. The results show that the VAT restitution process has been carried out in accordance with applicable procedures and regulations. The process is not considered difficult as long as taxpayers are compliant, administratively orderly, and supported by valid tax invoices. In addition, tax consultants play a crucial role in assisting taxpayers by ensuring complete documentation and a smooth audit process. The implications of this study indicate that an effective restitution process, supported by taxpayer compliance and professional assistance, can optimize the fulfillment of taxpayer rights and increase trust in the tax administration system.